The influence of impact source on variables associated with strain for impacts in ice hockey. Issue 7 (19th May 2019) - Post, Andrew; Dawson, Lauren; Hoshizaki, T. Blaine; Gilchrist, Michael D.; Cusimano, Michael D.
Abstract: Concussion can occur from a variety of events (falls to ice, collisions etc) in ice hockey, and as a result it is important to identify how these different impact sources affect the relationship between impact kinematics and strain that has been found to be associated to this injury. The purpose of this research was to examine the relationship between kinematic variables and strain in the brain for impact sources that led to concussion in ice hockey. Video of professional ice hockey games was analyzed for impacts that resulted in reported clinically diagnosed concussions. The impacts were reconstructed using physical models/ATDs to determine the impact kinematics and then simulated using finite element modelling to determine maximum principal strain and cumulative strain damage measure. A stepwise linear regression was conducted between linear acceleration, change in linear velocity, rotational acceleration, rotational velocity, and strain response in the brain. The results for the entire dataset was that rotational acceleration had the highest r 2 value for MPS (r 2 = 0.581) and change in rotational velocity for cumulative strain damage measure (r 2 = 450). When the impact source (shoulder, elbow, boards, or ice impacts) was isolated the rotational velocity and acceleration r 2 value increased, indicating that when evaluating the relationships between kinematics and strain based metrics the characteristics of the impact is an important factor. These results suggest that rotational measures should be included in future standard methods and helmet innovation and design in ice hockey as they have the highest association with strain in the brain tissues.